The Effect of ESG Disclosure on Financial Performance with Earnings Management as an Intervening Variable - Andini, Fizri; Mulyasari, Windu (PT Larva Wijaya Penerbit, 2024)
This study was conducted to examine the impact of ESG disclosure on financial performance with earnings management as an intervening variable. The final sample studied using purposive sampling technique in this study amounted to 160 data in the observation year 2019–2022 with companies in the manufacturing, real estate and mining sectors as the research population. The quantitative method was chosen in this study with data obtained from the Indonesian Stock Exchange, the official website of the sample company, and the Thomson Reuters Eikon website. The research model uses panel data regression analysis with the best model chosen is the Random Effect Model (REM), while to test the mediating variables is to use the Sobel test using a Sobel test calculator. From the tests conducted, the results prove that ESG disclosure has a significant positive effect on financial performance and earnings management cannot mediate the relationship between ESG disclosure and financial performance.